INFLUENCE OF TEMPERATURE AND pH ON MYCELIAL GROWTH AND CHLAMYDOSPORE PRODUCTION OF PADDY STRAW MUSHROOM Volvariella volvaceae (Bull. Ex Fr.) Sing - N. KIRAN KUMAR (The Journal of Research ANGRAU, 2016)
The present study was conducted to identify the optimum temperature and pH for both mycelial growth and chlamydospore production of Volvariella volvacea strain CBE TNAU 1505. The mycelium was subjected to varied temperatures (150C-400C) and pH (5-10). The optimum temperature that favoured the maximum mycelial growth and chlamydospore production of V. volvacea was 350C and 300C, respectively and the optimum pH range was 6 to 8. The temperatures below 200C and above 400C and the pH of below 6.0 and above 8.0 are not favourable for the growth and chlamydospore production of V. volvacea. Strain specific preference for temperature and pH optima to induce chlamydospores and stress metabolism needs future attention.